Serum Vascular Endothelial Growth Factor Levels and Uterine Fibroid Volume: Hubungan Kadar Serum Vascular Endothelial Growth Factor dengan Volume Mioma Uteri - Rajuddin Rajuddin; Ronald Oscar; Tengku P. Dewi (Indonesian Journal of Obstetrics and Gynecology, 2020)
Background: Tumor size is related to variations associated with molecular markers. In recent years, it has been reported that investigation of tumor volume has become very popular. Measurement of uterine fibroids volume is very important for treatment response. Objective: The aims of this study is to find the correlation of VEGF levels and uterine fibroids volume. Methods: Observational analytic study was carried out on 80 patients with uterine fibroids indicated myomectomy. Each sample was examined for VEGF levels and volume of myoma tissue post myomectomy was measured by using Archimedes' law. Correlation test using the Spearman test. Results: A total of 80 samples of patients were examined for VEGF levels and uterine fibroids volume. The median VEGF is 360 pg/mL, the median uterine fibroids volume is 325 ml. The Spearman’s test shows p values ​​(<0.01) and r (0.999). Conclusion: There is a significant correlation between VEGF levels and uterine fibroids volume. The higher the VEGF level, the greater the volume of uterine fibroids. Keywords: VEGF, uterine fibroids volume, Archimedes law *Corresponding author: Rajuddin e-mail: rajuddin@unsyiah.ac.id dan Ronald_drozz@yahoo.com